Clumps, Clusters and Classification - Bishop, Christopher (Computer Systems: Theory, Technology and Applications. A Tribute to Roger Needham, 2004)
Computer systems form the core of computing, as their combinations of hardware and software components function together to help program developers and end-users achieve goals of managing and accessing information in all its forms. Roger Needham, in a distinguished career at Cambridge University and Microsoft Research, was a pioneer of computer systems research and a noted innovator in the crucial area of system security. Computer Systems: Theory, Technology, and Applications presents a comprehensive edited survey of all aspects of the subject, with original contributions by more than 40 international leaders in the field. The book assembles a collection of short articles showing the state-of-the-art in systems, from formal calculi to mobile devices, from operating systems to distributed computing and security—while also honoring Needham’s important contributions.